2014
DOI: 10.1007/s13277-014-2457-0
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin suppresses the proliferation and induces apoptosis involving MAPKs and caspase-8/-9/-3 signals in human acute myeloid leukemia cells

Abstract: Nobiletin, a compound isolated from citrus fruits, is a polymethoxylated flavone derivative that was shown to have anti-inflammatory and anticancer activities in various solid tumors. The anticancer effect of nobiletin on nonsolid tumor remains unclear. Herein, the molecular mechanisms by which nobiletin exerts its anticancer effects on acute myeloid leukemia (AML) cells were investigated. The results showed that nobiletin suppressed cell proliferation in various types of AML cell lines. Moreover, nobiletin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…Aoki et al [99] found that nobiletin suppresses the cell proliferation by inhibiting Ras activity and MEK/ERK signaling cascade probably via a Ca 2+ -sensitive PKC-dependent mechanism. Hsiao et al [100] also reported that nobiletin suppressed cell proliferation in HL-60 AML cells via inducing cell-cycle arrest at the G0/G1 phase by suppressing extracellular signal-regulated kinase (ERK) activity. In another study, the nobiletin was shown to inhibit the proliferation of human pancreatic cancer cells (PANC-1) by inducing apoptosis via up-regulation of the proapoptotic protein bax and down-regulation of the anti-apoptotic proteins bcl-2 and p53 [101].…”
Section: Anti-proliferationmentioning
confidence: 99%
“…Aoki et al [99] found that nobiletin suppresses the cell proliferation by inhibiting Ras activity and MEK/ERK signaling cascade probably via a Ca 2+ -sensitive PKC-dependent mechanism. Hsiao et al [100] also reported that nobiletin suppressed cell proliferation in HL-60 AML cells via inducing cell-cycle arrest at the G0/G1 phase by suppressing extracellular signal-regulated kinase (ERK) activity. In another study, the nobiletin was shown to inhibit the proliferation of human pancreatic cancer cells (PANC-1) by inducing apoptosis via up-regulation of the proapoptotic protein bax and down-regulation of the anti-apoptotic proteins bcl-2 and p53 [101].…”
Section: Anti-proliferationmentioning
confidence: 99%
“…Flavonoids, a vast group of polyphenolic compounds ubiquitously present in plants [17], exhibit a wild spectrum of pharmacological properties and offer significantly protection against various cancers [18, 19]. As a member of flavonoids, nobiletin (5, 6, 7, 8, 3′ 4′-hexamethoxyflavone) has been proposed to have anti-cancer properties, including anti-angiogenesis, anti-proliferation, anti-metastasis and induced apoptosis in vitro and in vivo [2023]. Accumulate studies have showed that nobiletin also suppressed the expression of MMPs, which may serve as a promising agent for suppression of cancer invasion and metastasis [24].…”
Section: Introductionmentioning
confidence: 99%
“…), suppresses tumor proliferation (SMMC-7721, DU145, MDA-MB-435, MCF-7, HT29, and HTB43 cells, etc. ), and inhibits metastasis of tumor cells (HT-1080) [6,7,8,9,10,11,12,13,14]. Nobiletin also suppresses angiogenesis in human umbilical vein endothelial cells in vitro and in chicken chorioallantoic membrane and zebrafish in vivo models [15,16].…”
Section: Introductionmentioning
confidence: 99%